Perubahan Sosial Dalam Perkembangan Instagram Di Kalangan Mahasiswa - Septia Rani; Zulfa Khoirunisa; Andhita Risko Faristiana (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
Socio-cultural changes in the world of social media always occur due to the support of technological sophistication that has occurred to date. One of them is the use of Instagram for millennials. This study aims to find out how social change and the impact that occurs on students in using Instagram. This research was conducted using a case study approach by seeking qualitative data or methods. The results of the study show that the use of Instagram has an impact on the emergence of socio-cultural changes for students. First, they do not hesitate to share excessively in self-disclosure in cyberspace. Of course, this culture arose because of the presence of Instagram as a social media that can be accessed by anyone. Second, students are unable to provide boundaries between private and public spaces, so that Instagram currently also has influence as a channel or media in complementing relationships between people, and at the same time Instagram is part of the lifestyle that students choose when communicating. using advanced technology.